2022
DOI: 10.1038/s41598-022-06490-3
|View full text |Cite|
|
Sign up to set email alerts
|

Healthy working life expectancy at age 50 for people with and without osteoarthritis in local and national English populations

Abstract: Retirement ages are rising in many countries to offset the challenges of population ageing, but osteoarthritis is an age-associated disease that is becoming more prevalent and may limit capacity to work until older ages. We aimed to assess the impact of osteoarthritis on healthy working life expectancy (HWLE) by comparing HWLE for people with and without osteoarthritis from ages 50 and 65 nationally and in a local area in England. Mortality-linked data for adults aged ≥ 50 years were used from six waves (2002–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…This work makes a methodological contribution on the number and nature of covariates that may feasibly be analysed together using this approach. Smaller differences between subpopulations were observed in this study than were identified previously using the IMaCh approach 11 , 25 , which is considered to be methodologically sound but has restrictively high data requirements 73 , 74 .…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This work makes a methodological contribution on the number and nature of covariates that may feasibly be analysed together using this approach. Smaller differences between subpopulations were observed in this study than were identified previously using the IMaCh approach 11 , 25 , which is considered to be methodologically sound but has restrictively high data requirements 73 , 74 .…”
Section: Discussioncontrasting
confidence: 46%
“…Sensitivity analyses indicated that aHRR results were robust to the use of a simplified 3-state HWLE model compared to the full 5-state model previously published 11 , 25 . The higher HWLE estimates resulting from alternative ADL-based health operationalisation despite higher age HRR for transition the from healthy and working to unhealthy and/or not working (transition 1–2) and similar age HRRs for other transitions is likely to reflect different proportions of the population classed as a healthy at age 50.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…15 This is supported by numerous loading studies ranging from those examining the impacts of joint immobilization to those examining the outcomes of excessive joint loading 16 and others that imply that both too little movement as well as excessive repetitive movements can foster cartilage damage or render the bone beneath this tissue noncompliant 17 with dire functional and pain consequences, even if the individual is initially in good health, and especially if the older adult already suffers from osteoarthritis of one or more joints, 18 and is a woman. 19 In addition, while often overlooked, a host of prior economic factors, 20 as well as age, trauma, and obesity 21,22 may have a collective negative impact on the complex manifestations of osteoarthritis, including possible emergent problems of joint instability, muscle and bone attrition, excess functional disability, and impairments of those sensory perception mechanisms that serve joints and are designed to foster protection against undue loads and the high risk of moderate to severe joint injury, common in vulnerable adults.…”
Section: Osteoarthritismentioning
confidence: 99%
“…paid work) is important for the health and well-being of people with rheumatic and musculoskeletal disorders (RMDs). Yet they have a shorter healthy working life expectancy [ 1 ] and are less likely to be employed compared with those without long-term health conditions [ 2 ]. Working people with RMDs can struggle to manage work, leading to presenteeism (i.e.…”
Section: Introductionmentioning
confidence: 99%